Fully invariant subgroups of an infinitely iterated wreath product - Leshchenko, Y.L. (Algebra and Discrete Mathematics, 2011)
The article deals with the infinitely iterated wreath product of cyclic groups Cp of prime order p. We consider a generalized infinite wreath product as a direct limit of a sequence of finite nth wreath powers of Cp with certain embeddings and use its tableau representation. The main result are the statements that this group doesn't contain a nontrivial proper fully invariant subgroups and doesn't satisfy the normalizer condition.